2002
DOI: 10.1007/s11663-002-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibrium data and liquidus for the system “MnO”-CaO-(Al2O3 + SiO2) at Al2O3/SiO2 = 0.41

Abstract: Phase-equilibrium data and the liquidus for the system "MnO"-CaO-(Al 2 O 3 -SiO 2 ) at a manganeserich alloy saturation have been determined in the temperature range from 1423 to 1723 K. The results are presented in the form of a pseudoternary section "MnO"-CaO-(Al 2 O 3 ϩ SiO 2 ) with an Al 2 O 3 / SiO 2 weight ratio of 0.41. The following primary phases are present in the range of conditions investigated: 3Al 2 O 3 и2SiO 2 ; SiO 2 ; MnOиAl 2 O 3 и2SiO 2 ; (Mn,Ca)OиSiO 2 ; 2(Mn,Ca)OиSiO 2 ; MnOи Al 2 O 3 ; (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
4
16
1
Order By: Relevance
“…Finally, the five composition points from the present study (Table 1) at which only a single liquid phase was observed at these temperatures are also plotted. It can be seen that the calculations are in good agreement with the present experi- 26) Experimental points from Roghani et al 26) and from the present study were measured at Al 2 O 3 /SiO 2 weight ratios over the range 0.34 to 0.46. 26,27) ; ٗ and ᭛ represent gehlenite and anorthite, respectively, from the present study.…”
Section: Phase Diagrams Of Thesupporting
confidence: 89%
See 4 more Smart Citations
“…Finally, the five composition points from the present study (Table 1) at which only a single liquid phase was observed at these temperatures are also plotted. It can be seen that the calculations are in good agreement with the present experi- 26) Experimental points from Roghani et al 26) and from the present study were measured at Al 2 O 3 /SiO 2 weight ratios over the range 0.34 to 0.46. 26,27) ; ٗ and ᭛ represent gehlenite and anorthite, respectively, from the present study.…”
Section: Phase Diagrams Of Thesupporting
confidence: 89%
“…It can be seen that the calculations are in good agreement with the present experi- 26) Experimental points from Roghani et al 26) and from the present study were measured at Al 2 O 3 /SiO 2 weight ratios over the range 0.34 to 0.46. 26,27) ; ٗ and ᭛ represent gehlenite and anorthite, respectively, from the present study. mental points, but are in agreement with the points of Roghani et al 26) only for the monoxide liquidus.…”
Section: Phase Diagrams Of Thesupporting
confidence: 89%
See 3 more Smart Citations